Artificial Intelligence and Spirituality: Can AI Understand the Divine in Sufism? - Iqbal Ramadhan Irsyad Yudiono; Danur Putut Permadi (LaKaspia, 2025)
Amid the rapid advancement of artificial intelligence (AI) across various domains of life, philosophical and theological questions arise regarding the limitations of AI in understanding the spiritual dimensions of human existence, particularly within the tradition of Islamic Sufism. This research aims to explore the ability of AI to comprehend and represent transcendental spiritual meanings, and to analyze the limitations of AI from spiritual and metaphysical perspectives. Using a qualitative phenomenological approach, data were collected through documentations. The findings reveal that although AI is capable of mimicking religious knowledge verbally, it remains fundamentally incapable of grasping and reflecting esoteric aspects of Sufism, such as the experiential connection with the Divine, due to its lack of consciousness, intuition, and spiritual essence. True spiritual meaning can only be accessed through inner experience and spiritual practice —not through algorithmic processes. In conclusion, this study affirms that artificial intelligence cannot replace the role of spiritual experience in Sufism and highlights the need for a humanistic and ethical approach in the development of technology. The research contributes to the interdisciplinary discourse between Sufism, Islamic philosophy, and modern technology, offering a critical reflection on the epistemological boundaries of AI in religious contexts.